Sarekat Islam Madura: Between Social Religious and Political Movements, 1913 – 1920 - Iswahyudi (Britain International for Academic Research (BIAR) Publisher, 2022)
Madura during the colonial period or at the turn of the 20th century, indicated that it was not a fertile ground for mass mobilization. Starting from the community because it is almost completely divided as a result of scattered settlements and scarcity of resources. The movement that rejects various kinds of prejudice is shown at a glance with the development of the Madura branch of the Sarekat Islam led by the hajj, so that the Dutch government still feels the symptoms of Islamophobia and is also supported by the small people, in this case oreng kenek with its distinctive ideology such as milleniarism and Islamic messianism. . The limitations of each kyai are closer to the peasants from the village, whereas a haji is generally a trader who lives in urban areas. So in this case a kyai is considered a power broker to mobilize the population, especially from among the peasants, while a haji acts as a cultural broker, especially for the revival of Islam. Related to the ideals of self-determination in politics, it is a reflection of the capabilities of the Madurese Sarekat Islam figures to the various social changes or modernity that were taking place at that time.